Główne problemy diecezji siedleckiej po odzyskaniu niepodległości w pismach i działaniach bp. Henryka Przeździeckiego - Krawczyk, Roman (Warszawskie Studia Teologiczne, 2019)
The person of Henryk Przeździecki, the first bishop of the restored Diocese of Podlachia (i.e. Siedlce) is worth reminding in the 200-th aniversary of the foundation of the Diocese, due to his enormous services for the Church in Poland. The paper is divided into four parts. The first part is devoted to the biography of the bishop, and the second concentrates on the bishop’s activity related to the organisation and management of the diocese and as a member of the Episcopate of Poland. The third part presents an outline of the central institutions of the diocese organized by bishop Henryk Przeździecki. The last part focuses on the problem of Neo-Union in the Diocese of Siedlce.